2009
DOI: 10.1007/s10995-009-0544-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Birth Certificate Prepregnancy Weight and Height Among Women Enrolled in Prenatal WIC Program: Florida, 2005

Abstract: To investigate the reliability and validity of weight, height, and body mass index (BMI) from birth certificates with directly measured values from the Women, Infants, and Children (WIC) Program. Florida birth certificate data were linked and compared with first trimester WIC data for women with a live birth during the last quarter of calendar year 2005 (n = 23,314 women). Mean differences for weight, height, and BMI were calculated by subtracting birth certificate values from WIC values. Reliability was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 23 publications
3
73
0
Order By: Relevance
“…Even items that had large discrepancies between the birth certificate and the medical record, such as hypertension in NYC and PROM in Vermont, had excellent or near-excellent specificity and NPV. Our results for Medicaid coverage are consistent with two previous state-based studies-one conducted in California, 11 which found an overall agreement of 95.8% between birth certificate and women's self-report on a survey; and the other in Iowa, 9 which found a sensitivity of 86.3% and specificity of 91.9% for birth certificates using matched Medicaid claims records as the gold standard. Our sensitivity estimates for Medicaid coverage, however, were generally higher than that found in an NCHS study of eight hospitals in two states, where sensitivity for Medicaid coverage in each hospital ranged from ,50% to .90%.…”
Section: Discussionsupporting
confidence: 90%
“…Even items that had large discrepancies between the birth certificate and the medical record, such as hypertension in NYC and PROM in Vermont, had excellent or near-excellent specificity and NPV. Our results for Medicaid coverage are consistent with two previous state-based studies-one conducted in California, 11 which found an overall agreement of 95.8% between birth certificate and women's self-report on a survey; and the other in Iowa, 9 which found a sensitivity of 86.3% and specificity of 91.9% for birth certificates using matched Medicaid claims records as the gold standard. Our sensitivity estimates for Medicaid coverage, however, were generally higher than that found in an NCHS study of eight hospitals in two states, where sensitivity for Medicaid coverage in each hospital ranged from ,50% to .90%.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, birth certificate data seem to be both reliable and valid when used for research purposes, with recall or reporting bias having minimal effect. 24 The BMI data are thought to be missing at random, because entry into the dataset depended on documentation by WA data entry staff using medical chart data, physician report, or maternal recall, and they should not be a source of bias. Moreover, our case definition may underestimate the prevalence of CKD in WA.…”
Section: Discussionmentioning
confidence: 99%
“…1 Limitation in intellectual ability corresponds to an intelligence quotient (IQ) of <70, described as mild (IQ 55-70), moderate (IQ [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], or severe to profound (IQ of <40). 2 The prevalence of ID in the general population is estimated to be approximately 1%, and among those with ID 85% are characterised as having mild ID.…”
Section: Introductionmentioning
confidence: 99%